PENGGUNAAN MEDIA APRON NUMBER DALAM MENGENALKAN KONSEP BILANGAN PADA ANAK DI TK KEMALA BHAYANGKARI 1 PONTIANAK - Ade Jusmiyanti; Aswandi Aswandi; Desni Yuniarni (Universitas Tanjungpura, 2020)
Abstract This study aimed to determine the effect of using the Apron Number media on the introduction of the concept of numbers for children aged 4-5 years at TK Kemala Bhayangkari 1 Pontianak. This study used a quantitative approach with experimental methods. The sample of this research is class A1 and A2, amounting to 14 children each as the experimental group and the control group. The data collection techniques used were observation and documentation and used descriptive analysis. The results of this study explained that the t value was 2.148, while the t value (table) with a significance level of 5% for one side and 0.025 (for two sides) with 26 degrees of freedom was 2.056. Because the value of t_count> t_ (table) (2.148> 2.056), the null hypothesis was rejected. Furthermore, there is an effect of the use of the Apron Number media on the introduction of the concept of numbers for children aged 4-5 years at Kemala Bhayangkari 1 Kindergarten, Pontianak. If calculated using the coefficient of determination the effect is 81.90%. The conclusion, that the Apron Number media has an effect on the introduction of the concept of child numbers. Keywords: Introduction to the concept of number, Media Apron Number